SEDENTARY LIFESTYLE AND COMORBIDITIES: OVERVIEW OFUPDATED EVIDENCE OF POTENTIAL HEALTH RISK - Prambudi, Aristanto; Rofi’ah, Ika Ainur (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2025)
Sedentary lifestyle has become a significant public health concern worldwide, contributing significantly to the rising prevalence of non-communicable diseases such as hypertension, type 2 diabetes (T2DM), and obesity. Characterized by prolonged sitting or low-energy activities, it has been associated with physical and psychological health risks. This literature review examines and synthesizes recent evidence on the relationship between sedentary lifestyle and the development of common comorbidities. A literature review design was employed, sourcing relevant full-text articles published between 2018 and 2025 from databases including ScienceDirect, EBSCOhost, ProQuest, and Google Scholar. Inclusion criteria focused on studies that investigated the association between sedentary lifestyle and adult comorbidities, using quantitative, observational, and meta-analytical methods. The results of this study included eight peer-reviewed studies, including observational, cross-sectional analyses, systematic reviews, and randomized clinical trials. The findings showed a significant association between sedentary lifestyles and a variety of comorbidities, including hypertension, T2DM, and obesity. This literature review confirms that a sedentary lifestyle significantly contributes to the risk of hypertension, T2DM, and obesity. As sedentary lifestyles become increasingly common, particularly among the elderly, it is crucial to implement public health initiatives, encourage active living, and develop culturally appropriate interventions to reduce the impact of associated non-communicable diseases.